Apical sealing ability of MTA in liquid to powder ratios and packing methods - Oraie, Ehsan; Ghassemi, Amir Reza; Eliasifar, Gholamhosein; Sadeghi, Masoumeh; Shahravan, Arash (Iranian Endodontic Journal, 2011)
Introduction: In apical surgery, after apicoectomy and retro-preparation of canal, a retrofil material is applied to seal the apical region of the root canal. Mineral trioxide aggregate (MTA) is the gold standard material for this purpose. Changing water/powder ratios of MTA affects its properties. The purpose of this in vitro study was to determine the effect of liquid/powder ratio of retrofil MTA on apical dye leakage, and also compare two packing techniques for MTA. Ma